Anaerobic digestion of food wastes for biogas production - Chen, Xiguang; Romano, Rowena T.; Zhang, Ruihong (International Journal of Agricultural and Biological Engineering, 2010)
Abstract: Five types of food wastes were investigated as feedstock for a potential centralized anaerobic digester system in the area of Sacramento, California to produce biogas energy. The wastes were from a soup processing plant, a cafeteria, a commercial kitchen, a fish farm, and grease trap collection service. Digestibilities of the food wastes, individually and in mixtures, were conducted at mesophilic (35